Determinants of Literacy Levels in Indonesia - Fatmawati, Fatmawati (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2023)
The Indonesian government has made efforts to increase literacy rates in Indonesia by providing literacy education program services and developing the community's reading culture. This research aims to find out the influence of the number of schools, electrification level, GRDP and education on literacy in each province in Indonesia. The data in this research comes from the Central Statistics Agency for the period 2020-2022. This research uses panel data from 34 provinces in Indonesia. This research uses panel data combined with time series data from 2020-2022 and cross section data in 36 provinces in Indonesia. The dependent variable in this study is literacy, while the main independent variable here is the level of electrification. The results of this research show that the level of electrification and education has a positive and significant effect on literacy, while GRDP has a negative and significant effect on literacy.